2017
DOI: 10.6007/ijarbss/v7-i5/2883
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and Performance of Micro Enterprises in Moshi Tanzania

Abstract: Social media are gaining popularity and are increasingly used in regular operations of many organizations, including Micro Enterprises (MEs). Several studies have thus developed interests on investigating the impact of social media in MEs. Unfortunately most of the existing studies either did not consider performance factor of MEs or were not done in the context of developing counties like Tanzania. It is on this ground that this study explored how social media influence the MEs' performance in the context of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 3 publications
0
9
0
2
Order By: Relevance
“…Several studies (e.g. Kazungu, Matto, and Massawe, 2017;Kazungu and Panga, 2015;Ngugi, 2012) have found that SMEs are the main engines for growth and economic development of a county. SMEs significantly contribute to County's GDP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies (e.g. Kazungu, Matto, and Massawe, 2017;Kazungu and Panga, 2015;Ngugi, 2012) have found that SMEs are the main engines for growth and economic development of a county. SMEs significantly contribute to County's GDP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The regression analysis shows that the SMU has a significant effect on financial performance among microfinance institutions in terms of revenue earning growth. Kazungu et al (2017) explored how SM influence the Micro Enterprises' (MEs) performance in Moshi, Tanzania in the context of customer's base, sales growth, profit maximization, and brand improvement. Data were collected with the use of interview and questionnaire among owner-managers of ninety MEs.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Although this fact, however this research conceptualizes BP, based on satisfying the stakeholders, as having seven facets: profitability (PROF), growth (GRTH), market value (MV), customer satisfaction (CS), employee satisfaction (ES), environmental performance (EP) and social performance (SP) (Santos and Brito, 2012). On the other hand, a close look at the literature of SMU demonstrates that questionnaire measures have been adopted by numerous researchers to measure SMU (Kazungu et al, 2017;Dodokh, 2017;Ahmad et al, 2018). Although questionnaire measures are frequently utilized in the prior studies, however this research have used total fans of Facebook pages as a proxy for SMU of banking sector in MENA region.…”
Section: Measurement Of Variablesmentioning
confidence: 99%
“…Através do WhatsApp, os utilizadores podem também fazer chamadas telefónicas de som e imagem (videochamadas) grátis por meio de uma conexão com a internet. Actualmente é propriedade da Facebook, Inc. A literatura evidencia que o WhatsApp é uma ferramenta muito utilizada pelos jovens (KAZUNGU; MATTO, 2017), pelo que vale a pena investigar o quanto esta ferramenta pode contribuir para a coleta de dados em pesquisas cujo público alvo são justamente os jovens.…”
unclassified
“…Em 2018, o WhatsApp foi escolhido como método de recolha de dados qualitativos sobre o uso de contraceptivos em jovens de Malawi. O argumento para a utilização do WhatsApp como ferramenta para obter informação sobre os adolescentes foi o facto de esta aplicação ser bastante popular entre os jovens de Malawi (KAZUNGU; MATTO, 2017). Assim, era oferecido aos jovens uma forma de obter informação sensível que pudesse ser mais difícil de partilhar numa entrevista presencial.…”
unclassified